2018
DOI: 10.1001/jamapsychiatry.2017.4307
|View full text |Cite
|
Sign up to set email alerts
|

Association of DSM-5 Betel-Quid Use Disorder With Oral Potentially Malignant Disorder in 6 Betel-Quid Endemic Asian Populations

Abstract: This international study gathered data about BQ users across 6 Asian populations, and it demonstrates that DSM-5 symptoms could fulfill a BUD construct. Most current Asian users of BQ already have BUD, which is correlated with risk of OPMD. Among individuals with moderate to severe BUD who used BQ, tolerance and a larger amount or longer history of BQ use are the key symptoms that correlated with enhanced risk of OPMD. These findings play an important role in providing a new indication of an additional psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…BQ is now the fourth most commonly consumed psychoactive substance in the world, following only alcohol, nicotine, and caffeine (5,6). A recent study with a large sample size in 6 Asian populations revealed a vast prevalence of BQ use in these counties (typically over 10%) (7). BQ use is reported to be highly associated with oral sub-mucous fibrosis and oral cancer (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BQ is now the fourth most commonly consumed psychoactive substance in the world, following only alcohol, nicotine, and caffeine (5,6). A recent study with a large sample size in 6 Asian populations revealed a vast prevalence of BQ use in these counties (typically over 10%) (7). BQ use is reported to be highly associated with oral sub-mucous fibrosis and oral cancer (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of researches have suggested that intensive BQ use shows similar symptoms of other addictive disorders. First, in the Asian Betel-quid Consortium study of 8922 participants from 6 countries, betel-quid use disorder was reported to meet DSM-V criteria for substance use disorder and had a high prevalence among users of betel-quid (7). Another study suggested that the 12-month prevalence of BQ use disorder was 18.0%, which exceeded that reported for DSM-V defined drug use disorder (3.9%) (13) and was comparable to the results of alcohol (13.9%) and nicotine (20.0%) use disorders (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the lowest quartile of PVC burden (0%–0.002%), patients having the highest quartile of PVCs burden (0.123%–17.7%) were identified to have a higher risk of decreased LVEF, congestive heart failure, and mortality [ 39 ]. BQ is an addictive substance that can induce BQ use disorder [ 7 ]. In this investigation, BQ chewing revealed a significant effect on high level of PVC.…”
Section: Discussionmentioning
confidence: 99%
“…This substance has been habitually consumed in six Asian populations with a prevalence of 9.8–43.6% in men and 1.8–46.8% in women [ 4 ]. In large-scale psychiatry studies, chronic BQ chewers were observed to have dependence symptoms and the related symptoms meet the DSM -5 criteria for a substance use disorder [ 5 , 6 , 7 ]. Epidemiological investigations have indicated that BQ users were at a higher risk of contracting systematic diseases that occurred in the brain, heart, lungs, gastrointestinal tracts, and reproductive organs [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Lee et al validated BQ use disorder (BUD) among addictive BQ users using DSM-5 diagnosis of 'use disorder' in six BQ endemic Asian populations (Lee et al, 2018). For Taiwan, Mainland China, Malaysia, Indonesia, Nepal and Sri Lanka, the 12-month prevalence of DSM-5-defined BUD were determined to be 56−99% of current users (Lee et al, 2012a(Lee et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%